Harmonization of monographic standards is needed to ensure the quality of Chinese medicinal materials - Zhao Sandy; Leung Kelvin; Chan Kelvin (BMC, 2009)
Abstract This article provides an overview on the regulations of Chinese medicinal materials (CMMs) in various countries and regions. Harmonization of CMM monographs would provide standards for the quality control of CMM products and play an important role in the modernization and globalization of Chinese medicine. A harmonized regulatory system would improve the quality of CMMs thereby ensuring the safety of the products and assisting Chinese medicine practitioners in their practice. The fast growing demand worldwide for traditional medicines calls for harmonized monographic standards to safeguard the safety and quality of CMM products.